PENGARUH METODE PEMBELAJARAN DAN RESPON TERHADAP KEMAMPUAN SOLFEJIO MUSIK PADA SISWA - RETNOWATI, TJUT ETTY (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
The purpose of this research is to find out empirically the influence of learning method and response capabilities Solfejio music.Solfejio capacity is a form of music practice which includes (is composed of): Sight Reading, Sight Singing, Ear Training, Sight Playing or Prima Vista. This research focuses on Sight Reading and Sight Singing for Grade II Primary Students. Significant means of interaction effect between learning methods and response capabilities Solfejio music.Zoltan Kodaly learning method with high response would allow student to upgrade its Solfejio capacity.The study result can be used as input, consideration, and development of music art teacher of elementary student in general.Keywords: the influence learning method, response, solfeijo